Pendidikan dan Nasionalisme: Analisis Pemikiran Raden Ajeng Kartini Sebagai Pahlawan Emansipasi Perempuan - Nuril Karomatillah Arifah; Almi Novita (Institut Kariman Wirayudha Sumenep, 2023)
This study aims to analyze Raden Adjeng Kartini's thoughts as a Hero of Women's Emancipation with a focus on the relationship between education and nationalism. The aim of this research is to outline Kartini's views regarding education, gender equality and modernity as important elements in advancing women's emancipation in Indonesia. This research uses library research which involves research through previous research, journals, the web, historical documents and related literature discussing issues of gender, education and nationalism to support this analysis. Kartini's views on education emerged as the main foundation for achieving women's emancipation. He considered education to be the main key to raising the dignity of women, providing equal opportunities with men, and freeing them from the shackles of restrictive traditions. Apart from that, Kartini strongly criticized the practice of polygamy which she considered a form of gender injustice and hampered women's development. He views that gender equality must be sought in society, both in access to education and in obtaining equal social rights. The results of the analysis show that Kartini encouraged gender equality and tried to achieve a balance between Western modernity and Javanese traditional values. The implication of this understanding is the importance of integrating Kartini's values in education policies to support women's emancipation and build an inclusive society. In conclusion, Kartini's thoughts have strong relevance in the context of education and nationalism, and provide direction for efforts towards equality and social progress in Indonesia